HUBUNGAN DUKUNGAN KELUARGA, PENGETAHUAN DAN SIKAP IBU DENGAN KESIAPAN MENGHADAPI PERUBAHAN PADA MASA PREMENOPAUSE - Novita Sari Nopita; Murdinigsih Murdinigsih; Sri Handayani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Premenopause is a transitional phase experienced by womentowards menopause, this phase is a physiological condition in women who have entered the aging process, which is characterized by decreased levels of the hormone estrogen from the ovaries. The period can occur for 2-5 years before menopause. This study aims determinan the relationship support mothers knowledge and attitude with village change readliness in Premenopause district, Padang city, capacity city age 45-50 years old years 2021.This type of research is Qualitative research with a Cross-Sectional research design approach, namely the type of research that emphasizes the measurement time of observation of the independent and dependent variabels at the same time.The population and sample of the study were all premenopause women in Padang city aged 45-50 years totaling 36 people. The result showed that there was a relationship between family support,knowledge and attitude of mothers simultaneously with readlines to accept change in the Premenopause period of mothers aged 45-50 years.    Readdiness to face premenopause changes to mothers aged 45-50 years.   Keywords         : Premenopause, Family Support, Knowledge, Attitude